2019
DOI: 10.1158/1078-0432.ccr-19-1009
|View full text |Cite
|
Sign up to set email alerts
|

Decreased NOTCH1 Activation Correlates with Response to Ibrutinib in Chronic Lymphocytic Leukemia

Abstract: Purpose: Ibrutinib, a Bruton tyrosine kinase inhibitor (BTKi), has improved the outcomes of chronic lymphocytic leukemia (CLL), but primary resistance or relapse are issues of increasing significance. While the predominant mechanism of action of BTKi is the B-cell receptor (BCR) blockade, many offtarget effects are unknown. We investigated potential interactions between BCR pathway and NOTCH1 activity in ibrutinib-treated CLL to identify new mechanisms of therapy resistance and markers to monitor disease respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…Ibrutinib treatment has been shown to reduce NOTCH1 activation, most pronounced at 12 months of continuous therapy. 13 In the setting of cardiac ischemia, NOTCH1 -activated bone marrow–derived mesenchymal stem cells promote CM survival through an antifibrotic mechanism. 14 Although this hypothesis is predicated on myocardial injury, subclinical ischemia is possible in a cohort with a median age over 75.…”
Section: Discussionmentioning
confidence: 99%
“…Ibrutinib treatment has been shown to reduce NOTCH1 activation, most pronounced at 12 months of continuous therapy. 13 In the setting of cardiac ischemia, NOTCH1 -activated bone marrow–derived mesenchymal stem cells promote CM survival through an antifibrotic mechanism. 14 Although this hypothesis is predicated on myocardial injury, subclinical ischemia is possible in a cohort with a median age over 75.…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant NOTCH1 signaling in CLL cells regulates several genes that influence key biological aspects of neoplastic cells, such as apoptosis, cell growth, cell migration, interactions with the microenvironment and B Cell Receptor (BCR) activation. It has been shown that a synergistic cooperation between NOTCH1 and BCR strongly supports the survival/proliferation of CLL cells and contributes to a progression of the disease ( 11 ) but also to the transformation into Richter’s syndrome (RS) ( 12 ). Furthermore, it has been recently shown that ligand-dependent activation of NOTCH1 signaling, via constitutive PI3K/AKT activation, promotes CLL transformation towards RS in Eμ- TCL1 mice in vivo ( 13 ), thus further supporting the association between non-mutational NOTCH1 activation and a poor prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…RO4929097 inhibited the NOTCH3/NR4A1 axis, upregulated the NOTCH2/FCER2 (CD23) axis, and enhanced the NOTCH2/CSL transcription factor complex ( Figure 5 B, right panel), which stands in sharp contrast to the effect of gliotoxin. The NOTCH1 target gene MYC was downregulated by RO4929097 ( Figure 5 B, right panel) [ 9 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, compounds that interfere with B-cell activation might affect the expression of both NOTCH receptors in CLL cells. This would explain why CLL cells pre-treated with Duvelisib (a dual PI3K-δ/γ inhibitor) [69] or Ibrutinib (a Bruton's tyrosine kinase inhibitor) [2,44] express lower amounts of CD23 and NOTCH3 and are less sensitive to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation